Spontaneous bacterial peritonitis due to streptococcus pneumoniae: a case report - Poudel, Bipin; Shrestha, Shubham; Pandey, Bimal; Acharya, Pawan; Pandey, Rabindra Raj (Journal of Patan Academy of Health Sciences, 2023)
Despite not being a normal gastrointestinal flora, Streptococcus pneumoniae can be the causative agent of Spontaneous Bacterial Peritonitis (SBP) in clinical setting. Patient present with fever, progressive abdominal pain, swelling of limbs, abdomen or both. It is mainly diagnosed by ascitic fluid tapping and its cell count along with culture and sensitivity. This condition has very good response with antibiotics as per culture reports. Here, we present a common case of SBP caused by an uncommon pathogen Streptococcus pneumoniae.